The Concept of Waterfront Management Based on Disaster Mitigation - Olivia Oktorie; Dedi Hermon; Indang Dewata (Pascasarjana, Universitas Negeri Padang, 2020)
The concept of integrated waterfront management is a development concept that involves all stakeholders such as government, private and public as well as stakeholders in the waterfront city area. So that waterfront management leads to a planned development approach in the coastal area. With the concept of integrated waterfront management, it is hoped that stakeholders in the waterfront city area can manage development that maintains a balance and can be tolerated by the community and the environment. Keywords: Waterfront, Disaster, Management